Peran Self Efficacy dan Student Engagement Terhadap Learning Outcomes Mahasiswa Magister PJJ Manajemen Universitas Ciputra Surabaya - Endi Sarwoko; Hastuti Naibaho (Universitas Sarjanawiyata Tamansiswa, 2026)
: Online learning, especially distance education, aims to provide broader opportunities for the community to pursue higher education. Although the quality standards for the implementation of distance education are the same as the curriculum of the organizing study programs, there is still debate over whether the learning outcomes and the quality of graduates are the same as regular study programs, considering that all learning activities are conducted online. The research aims to obtain empirical evidence of the role of self-efficacy and student engagement on learning outcomes in the implementation of distance learning, as well as to analyze the role of student engagement as a mediator of the influence of self-efficacy on learning outcomes. The research uses a quantitative method with a survey on active students of the distance learning management master's program at Universitas Ciputra Surabaya. Data were collected using an online questionnaire, and the data were analyzed with PLS-SEM. The research results revealed that learning outcomes in the implementation of distance learning are determined by self-efficacy and student engagement. Self-efficacy not only has a direct impact on learning outcomes but also enhances student engagement, which in turn contributes to learning outcomes. The research is relevant to the Social Cognitive Theory, which posits that individual behavior is the result of the interaction between personal factors, behavior, and the environment. Additionally, the research has implications for the importance of increasing student engagement in the online learning process, starting from curriculum design, semester learning plans, and learning activities.